ANALISA SEMIOTIKA FERDINAND DE SAUSSURE TERHADAP LIRIK LAGU “SAKURA NO HANABIRATACHI” KARYA JKT48 - Fahmi Handiansyah; Muhammad Rizki Fadhillah, Calvin Eka Sambora, Zaky Aulia Drajat, Riza Fahlapi (ADISAM PUBLISHER, 2024)
This study aims to interpret the meaning of farewell contained in the lyrics of the song